Visual Quality of Streetscape Arrangement in Enhancing Tourist Attraction in the Historic Street Corridor of Karangturi Village, Lasem - Nisa Nurillah, Luthfiyatun; Ernawati, Jenny; Antariksa (Journal of Indonesian Tourism and Development Studies, 2025)
The street corridors in historic areas play a crucial role in enhancing tourism appeal and have a significant impact on creating memorable spatial experiences. In Karangturi Village, Lasem, visual elements not only represent historical and local cultural values but also serve as key attractions that enrich visitors’ overall experiences. This study aims to examine the visual quality of the streetscape along the historic corridor in Karangturi Village, Lasem, using a quantitative approach through questionnaires distributed to 185 visitors. The assessment focuses on five aspects of visual landscape quality: dominance, unity, continuity, uniqueness, and rhythm. The results indicate that the visual elements of the streetscape are highly rated and align with the historical character of the area, particularly in the dominance of street lighting and the uniqueness of building designs. These findings suggest that visual landscape design functions not merely as an aesthetic component but also as a strategic instrument to support the development of heritage-based tourism.